Hormonal Contraception. Guideline of the DGGG, OEGGG and SGGG (S3 Level, AWMF Registry Number 015/015, January 2020) - Franik, Sebastian; Bauersachs, Rupert; Beyer-Westendorf, Jan; Buchholz, Tina; Bühling, Kai; Diener, Hans Christoph; Erath, Anke; Fischer, Ronald; Förderreuther, Stefanie; Franz, Heiko B.G.; Hach-Wunderle, Viola; Hadji, Peymann; et al. (Geburtshilfe und Frauenheilkunde, 2021)
Aims This is an official interdisciplinary guideline published and coordinated by the German Society for Gynecology and Obstetrics (DGGG), the Austrian Society for Gynecology and Obstetrics (OEGGG) and the Swiss Society for Gynecology and Obstetrics (SGGG). The guideline was developed for use in German-speaking regions and is backed by numerous professional societies and organizations. The aim of this guideline is to provide an evidence- and consensus-based overview of the diagnostic approach and the management of hormonal contraception based on a systematic evaluation of the relevant literature. Methods To compile this S3-guideline, a systematic search for evidence was carried out in PubMed and the Cochrane Library to adapt existing guidelines and identify relevant reviews and meta-analyses. A structured evaluation of the evidence was subsequently carried out on behalf of the Guidelines Commission of the DGGG, and a structured consensus was achieved based on consensus conferences attended by representative members from the different specialist societies and professions. Recommendations Evidence-based recommendations about the advice given to women requesting contraception were compiled. The guideline particularly focuses on prescribing contraceptives which are appropriate to women's individual needs, take account of her personal circumstances, and have few or no side effects.
CRIS-Team Scopus Importer:2021-02-26
Keywords: counseling; guideline; hormonal contraception; recommendations